The Model of capitalism of Hungary's dependent economy as compared to Other Visegrád countries - György, László; Oláh, Dániel (Public Finance Quarterly, 2023)
The theoretical school of thought known as ‘varieties of capitalism’ (VoC) grew significantly in popularity following the turn of the millennium. In the 2000s, it formed an excessively simplified typology, which was unable to integrate into its theoretical system the Central European economies located – both geographically and in the theoretical sense – between the opposite poles of the Estonian liberal market economy and the Slovenian coordinated market economy. For this reason, in 2009, Nölke and Vliegenthart created the category of dependent economies, by which they primarily meant the Visegrád countries. The distinguishing characteristic of the operating mechanisms of this type of capitalism is foreign capital. Nölke et al., however, fail to consider that within the group of dependent economies, Hungary found itself in a privileged position in the first twenty years following the political regime change, carrying out earlier, faster and more extensive privatization compared to other countries of the region. Our study presents with the help of its own set of criteria how, before 2008, the Hungarian economy could be regarded as a special, extreme case of a dependent economy.